Screening for diabetic retinopathy in pregnancy using photographic review clinics. Issue 4 (17th March 2013) - Hampshire, R.; Wharton, H.; Leigh, R.; Wright, A.; Dodson, P.
Abstract Aims To assess the efficacy and value of the National Institute for Health and Clinical Excellence guidelines for digital photographic screening for diabetic retinopathy in pregnancy using photographic review clinics. Methods Pregnant patients (n = 186) with known diabetes were screened at first antenatal visit and at 28 weeks' gestation, if no retinopathy was noted at first visit, or at other intervals if retinopathy was present. Two 45° images (disc‐centred and macula‐centred views) were taken in both eyes and graded by trained graders and by an ophthalmologist. Results Ninety‐three patients (50%) remained free of diabetic retinopathy throughout pregnancy. Eighteen (10%) presented with sight‐threatening retinopathy at their first antenatal screen and were referred to the hospital eye service. Fifty patients (27%) were shown to have relatively stable retinopathy throughout pregnancy, with only two patients deteriorating and requiring referral to hospital eye service. Twenty‐three (12%) failed to complete the screening protocol after their first screen. Conclusions The study showed that pregnant patients screened for retinopathy in an ophthalmic photographic diabetic review clinic achieved National Institute for Health and Clinical Excellence guidelines in the majority and were clinically safe. Only 1% of patients required referral to ophthalmology after their initial screen, thus avoiding unnecessary hospital eye service appointments.